Chromatin dynamics during interphase and cell division: similarities and differences between model and crop plants. (18th October 2019) - Pecinka, Ales; Chevalier, Christian; Colas, Isabelle; Kalantidis, Kriton; Varotto, Serena; Krugman, Tamar; Michailidis, Christos; Vallés, María-Pilar; Muñoz, Aitor; Pradillo, Mónica
Abstract : This review highligts unique and common themes in chromatin organization, modifications, and dynamics during development and stress situations in model plants and, in particular, crop plants. Abstract: Genetic information in the cell nucleus controls organismal development and responses to the environment, and finally ensures its own transmission to the next generations. To achieve so many different tasks, the genetic information is associated with structural and regulatory proteins, which orchestrate nuclear functions in time and space. Furthermore, plant life strategies require chromatin plasticity to allow a rapid adaptation to abiotic and biotic stresses. Here, we summarize current knowledge on the organization of plant chromatin and dynamics of chromosomes during interphase and mitotic and meiotic cell divisions for model and crop plants differing as to genome size, ploidy, and amount of genomic resources available. The existing data indicate that chromatin changes accompany most (if not all) cellular processes and that there are both shared and unique themes in the chromatin structure and global chromosome dynamics among species. Ongoing efforts to understand the molecular mechanisms involved in chromatin organization and remodeling have, together with the latest genome editing tools, potential to unlock crop genomes for innovative breeding strategies and improvements of various traits.